Legal limits to prioritisation in policing – challenging the impact of centralisation - Landström, Lena (Policing and society, 2020)
This article illustrates, through a combination of administrative and legal perspectives, how ambitions to centralise prioritisation decisions within a police organisation can be limited by the legal rules relating to crime investigations and public order policing. As a case study, we use the centralisation of the Swedish Police, a reform intending to reduce the previously far-reaching operational independence of regional police authorities in favour of a centralised and uniform single authority. Through this case study, we analyse the interaction between the legal and institutional frameworks of policing and prosecution, including positive obligations enshrined in the European Convention on Human Rights. We conclude that legal responsibilities affecting the Swedish Police may significantly limit the possibility for managers and officers to de-prioritise many cases and public order concerns, which, in turn, may limit the ability to divert resources to other—centrally prioritised—tasks. Failure to account for such limits may cause reform ambitions to collide with legal responsibilities in day-to-day operative policing. The results indicate that research into organisational reform and police prioritisation may benefit from a more systemic analysis of the legal and institutional factors limiting institutional discretion.